The Changes of Household Food Expense During COVID-19 Pandemic: A Case Study in Indonesia and Armenia - Relawati, Rahayu; Ariadi, Bambang Yudi; Bakhtiar, Ary; Minasyan, Sona (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 2 (2021): Vol.15, No.2, 2021DO - 10.24843/SOCA.2021.v15.i02.p16, 2021)
The Covid-19 pandemic has had an impact on the availability and distribution of food, but its impact on food consumption at the household level was not much known. The aim of the research was to analyze changes in food expense during the Covid-19 pandemic of cases in Indonesia and Armenia. Indonesian case used primary data in April-May 2020, at the beginning of the pandemic. Data were analyzed descriptively and paired t statistic test. The results showed that there was a change in consumption during the pandemic. The significant changes were an increase in the amount of rice consumption, an increase in food expense, and a decrease in the purchase of cooked meal. Snack purchases during the pandemic increased but not significantly. The Armenia case used secondary data from FAO. Regarding the COVID-19 pandemic, as well as the post-war crisis in the Republic of Armenia, it has had a negative impact on transportation, storage, sales, financial situation, access, and availability of agricultural products and labor markets. Thus, digital solutions for agricultural marketing, that is Digital Agriculture Marketplace Platform have been adopted. The conclusion was that the impact of the pandemic actually increased consumption needs. The recommendation that given was the support for food logistics transportation which very much needed in the pandemic era and more specifically supported by food distribution security.